Az államfők nemzetközi büntetőjogi felelősségre vonásának mai keretei - Papp, Nikolett (Debreceni Jogi Műhely, 2016)
Recent years the legal position of Heads of State and other very senior State representatives has received considerable attention from national and international courts, writers and practitioners. It is often said that the establishment of the ad hoc tribunals and the International Criminal Court, reflects a growing belief that the heads of State should be held accountable for serious violations of international humanitarian and human rights law. It has been argued that international law is now the stage where immunity should no longer apply in relation to serious international crimes. By contrast, others have emphasized the political and practical difficulties inherent in allowing national courts to serve as a tool for the transnational enforcement of penalties or damages for crimes committed abroad by the leaders and officials of foreign States. The resulting controversy has led the International Law Commission to include the topic ‘Immunity of State officials from Foreign Criminal Jurisdictions’ in its work programme. In my study I present the development of status of the Heads of State in international law, especially the criminal liability in the XX-XXI. Centuries. In this study I exhibit the development of the legal status of the heads of State and the actual questions in international law related to the criminal liability of heads of State and other senior State officials.